International Marketing Strategy as Determinants of Export Performance in Nepalese Handicraft Sector - Lingden, Binod (Journal of Advanced Academic Research, 2015)
Increased globalization of trade has led to a growing number of firm’s focus on high-growth export market. The spotlight on activity export has also attracted the attention of academics. This study aims at explaining the marketing strategy as determinants of export performance in Nepalese handicraft sector. Journal of Advanced Academic Research Vol.1(1) 2014: 85-87